Potential effects of adenosine triphosphate and melatonin on oxidative and inflammatory optic nerve damage in rats caused by 5-fluorouracil - Ahmet Mehmet Somuncu; Busra Parlak Somuncu; Ahmet Duhan Ozbay; Ibrahim Cicek; Bahadir Suleyman; Renad Mammadov; Seval Bulut; Tugba Bal Tastan; Taha Abdulkadir Coban; Halis Suleyman; Aliyev Aydin (International Journal of Ophthalmology)
AIM: To investigate the effects of adenosine triphosphate (ATP) and melatonin, which have antioxidant and anti-inflammatory activities, on potential 5-fluorouracil (5-FU)-induced optic nerve damage in rats. METHODS: Twenty-four rats were categorized into four groups of six rats: healthy (HG), 5-FU (FUG), ATP+5-FU (AFU), and melatonin+5-FU (MFU). ATP (4 mg/kg) and melatonin (10 mg/kg) were administered intraperitoneally and orally, respectively. One hour after ATP and melatonin administration, rats in the AFU, MFU, and FUG were intraperitoneally injected with 5-FU (100 mg/kg). ATP and melatonin were administered once daily for 10d. 5-FU was administered at a single dose on days 1, 3, and 5 of the experiment. After 10d, the rats were euthanized and optic nerve tissues were extracted. Optic nerve tissues were biochemically and histopathologically examined. RESULTS: ATP and melatonin treatments inhibited the increase in malondialdehyde (MDA) and interleukin-6 (IL-6) levels, which were elevated in the FUG. The treatments also prevented the decrease in total glutathione (tGSH) levels and the superoxide dismutase (SOD) and catalase (CAT) activities (P<0.001). This inhibition was higher in the ATP group than in the melatonin group (P<0.001). ATP prevented histopathological damage better than melatonin (P<0.05). CONCLUSION: ATP and melatonin have the potential to be used in alleviating 5-FU-induced optic nerve damage. In addition, ATP treatment shows better protective effects than melatonin.